Political legitimacy in Middle Africa : - Schatzberg, Michael G. (Indiana University Press, 2001)
Exploring the cultural underpinnings of political legitimacy, this title argues that the societies have a culturally-rooted template against which people come to understand the political legitimacy, or 'thinkability', of institutions, ideas, policies, and procedures. It also explores the role of the father-chief as head of the family.